Are Trade Preferences a Panacea? The Export Impact of the African Growth and Opportunity Act - Fernandes, Ana M.; Forero, Alejandro; Maemir, Hibret; Mattoo, Aaditya (World Bank, Washington, DC, 2019)
Does “infant industry” preferential access durably boost exports? Using country-product-year data for 1992–2017 and triple-differences regressions, we show that the African Growth and Opportunity Act (AGOA) enhanced apparel exports of African countries on average. But the impact leveled off after the Multi-Fiber Arrangement unleashed competition from Asian countries. Furthermore, the positive average impact masks regional heterogeneity: East Africa’s late-bloomers offset Southern Africa’s boom-bust pattern. Firm-level data reveal that even East Africa’s export growth was driven by entrants rather than incumbents who received large preference margins during the early AGOA years. Overall, the authors find little evidence that preferences durably boosted exports.